KNOWLEDGE AND PRACTICES REGARDING ULTRA-PROCESSED FOOD CONSUMPTION AMONG SECOND- AND THIRD-YEAR MEDICAL STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2025-2026 AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the knowledge and practices related to the consumption characteristics of ultra-processed foods among second- and third-year students who consume these foods at Hanoi Medical University in the academic year 2025-2026, and to analyze several associated factors.Methods: A cross-sectional descriptive study was conducted among 429 students using a self-administered questionnaire on the REDCap platform. Data were analyzed using Jamovi software with a statistical significance level of p < 0.05.Results: Students demonstrated relatively good knowledge of ultra-processed foods, with more than 80% correctly answering basic questions. However, the prevalence of high consumption of ultra-processed foods remained considerable. Lower monthly income was significantly associated with higher ultra-processed food consumption, and this group had lower mean knowledge scores. No statistically significant associations were found with gender, academic year, or current living arrangement.Conclusion: Although medical students had relatively good knowledge of ultra-processed foods, their consumption practices were not commensurate with this level of knowledge. Interventions combining food literacy enhancement and improvements to the university food environment are needed.
Keywords: Ultra-processed foods; knowledge; practices; medical students; Vietnam.